2021
DOI: 10.1111/jpy.13174
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Abscisic Acid Confers Salinity Tolerance in Chlamydomonas reinhardtii During Its Life Cycle

Abstract: The plant hormone abscisic acid (ABA) coordinates responses to environmental signals with developmental changes and is important for stress resilience and crop yield. However, fundamental questions remain about how this phytohormone affects microalgal growth and stress regulation throughout the different stages of their life cycle. In this study, the effects of ABA on the physiology of the freshwater microalga Chlamydomonas reinhardtii at its different life cycle stages were investigated. Exogenously added ABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Taken together, we demonstrated that MdWRKY70L improved the drought and salt stress tolerance in plants. Exogenous ABA improves salt stress tolerance in Lonicera lonicera and drought stress tolerance in Gynura cusimbua [ 56 , 57 ]. Studies have demonstrated that ABA-induced WRKY gene expression is often related to drought and salt stress [ 15 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, we demonstrated that MdWRKY70L improved the drought and salt stress tolerance in plants. Exogenous ABA improves salt stress tolerance in Lonicera lonicera and drought stress tolerance in Gynura cusimbua [ 56 , 57 ]. Studies have demonstrated that ABA-induced WRKY gene expression is often related to drought and salt stress [ 15 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In plants, ABA plays essential roles in multiple physiological processes as well as in responses to abiotic and biotic stresses [ 42 ]. In microalgae, the production of ABA is also related to the presence of stress conditions and is thought to also be involved in the regulation of microalgae growth and [ 41 , 43 ]. The exogenous application of ABA also leads to the accumulation of lipids in Chlorella [ 39 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggested that the phytormone abscissic acid (ABA) can support C. reinhardtii survival under high salt conditions. In fact, externally added ABA successfully reduced the deleterious effects of salt stress-induced oxidative stress, partially releasing the growth suppression and reducing ROS generation under salinities around 100 mM of NaCl [37,38]. In a recent study, ABA addition also fully recovered photosynthesis and prevented palmelloid formation under moderately high NaCl levels, whereas it supported the growth of C. reinhardtii at their gamete phase [38].…”
Section: Main Physiological Responses To Salinity Stress Exposurementioning
confidence: 98%
“…In fact, externally added ABA successfully reduced the deleterious effects of salt stress-induced oxidative stress, partially releasing the growth suppression and reducing ROS generation under salinities around 100 mM of NaCl [37,38]. In a recent study, ABA addition also fully recovered photosynthesis and prevented palmelloid formation under moderately high NaCl levels, whereas it supported the growth of C. reinhardtii at their gamete phase [38]. Thus, Chlamydomonas do respond to ABA even though there are no evidence suggesting it is internally synthesized, and ABA protects Chlamydomonas cells from high salinity, possibly as a signal molecule that mitigates the oxidative stress derived from these conditions.…”
Section: Main Physiological Responses To Salinity Stress Exposurementioning
confidence: 99%